Manajemen Marketing Sekolah dalam Meningkatkan Kualitas Input Siswa di Madrasah Aliyah Miftahul Midad Sumberejo Sukodono Lumajang - Sholicha, Syovinatus; Andriani, Eva (Published by the Postgraduate Program in Islamic Education Management, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, Indonesia, 2023)
Improving the quality of student input requires school marketing management that can be accepted by the wider community and is able to establish harmonious relationships with the community so that it can involve them actively in order to realize school and educational goals, work with the management team, and succeed in realizing school goals productively according to with stipulated conditions. School marketing management in carrying out cooperation is by building relationships, strengthening internal networks, intelligently utilizing the momentum of cooperation, training mass mobility and diversifying. So that by strengthening the management of the school or school will be superior. The results of this study are: 1) School marketing management in improving the quality of student input at Madrasah Aliyah Miftahul Midad Sumberejo Sukodono is carried out in several ways, namely through publication, socialization, collaboration with alumni and the mass media, 2) The results of school marketing management in improving the quality of student input from the last three years starting in 2018 there were 343 students, in 2019 it increased to 371 students and in 2020 it increased to 441 students. In terms of student quality, there has also been an increase, in 2018 students with excellent quality entered as many as 50 students, in 2019 as many as 65 students and in 2020 as many as 67 students, 3) The supporting factors are marketing management designed systematically, collaboration with professional teachers, Meanwhile the inhibiting factor is the delivery of information data to improve the image is still lacking, inadequate facilities and do not master information delivery techniques, limited time for school marketing administrators when serving the external public, the school's marketing function has not functioned properly.